Ecos de uma guerra ao norte : os impactos da Guerra de Secessão na aprovação da Lei do Ventre Livre no Brasil (1865 – 1871) - Mamedes, Giovanni Bezerra de Menezes (2021)
Despite the profound political, economic and social differences between the Empire of Brazil and the United States of America in the 19th century, the two countries had a common feature in their trajectories: both consolidated themselves as nations after their respective independences while expanding their slave agricultural economies. Therefore, the permanence of slavery was a link between the historical experiences of the Southern Empire and the Northern Republic. Considering this relation, this research starts from the premise that the abolition of slavery in the United States as a result of a violent civil war in 1865 shook the framework of stability in which slavery was sustained in Brazil. Our objective was to identify how the imperial political elite interpreted this event and what where its consequences for the fate of slavery in Brazil. To this end, we analyzed the minutes of the Senate, the Chamber of Deputies and the Council of State of the brazilian Empire between the years 1865 to 1871, namely, the year of the end of the Civil War in the United States and the year of the approval of the Free Womb Law in Brazil.